Assessment of the spectrum of enteric duplication cysts and their varied presentations - Bhatta, Priyamvadha; Tuteja , Neeraj (International Journal of Contemporary Pediatrics, 2025)
Enteric duplication cysts having an incidence of 1 in 4500 live births, are not often diagnosed antenatally. Patients who are eventually diagnosed, have a varying presentation, clinically and demographically, demographically and clinically. Classified as cystic and tubular, with the latter being radiologically difficult to detect on ultrasound. Differential diagnoses of mesenteric cysts and omental cysts. This prospective study was done over a two-year period, where patients who were diagnosed with enteric duplication cysts at Sir Padampat Institute of Neonatology and Child Institute, Jaipur were included. They were monitored from the time of diagnosis, assessing demographic data, preoperative status, surgical management, post operative treatment and follow up after discharge. Total14 patients were included, of which a majority were tubular variants of ileal duplication cyst. 3 patients had foregut duplication cysts (1 gastric, 2 oesophageal). The age ranged from 3 days to 10 years, with the average age of 2.2 years. Each child had a varying presentation, some of them presenting with complications like obstruction and perforation. The incidence was more in male, as compared to females (3.6:1 – male:female). Two children had associated anomalies (one had a congenital diaphragmatic hernia, and one had malrotation of the gut). In one child, a foregut duplication cyst was found to be communicating with a dilated segment of the jejunum, which was resected together. Enteric duplication cysts, can have a myriad of presentations, and other associated congenital anomalies. Further studies are required to identify attributing risk factors, regional incidence along with better awareness for antenatal screening.